UPAYA PEMERINTAH TURKI DALAM MENANGGULANGI PENGUNGSI DARI SURIAH TAHUN 2014-2016 - Maisyita Syafitri; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes how the Turkish state's role in tackling the Syrian refugees residing in Turkey in 2014-2016. The conflict in Syria that began in 2011, when there was a protests to depose the regime in Syria and the cause of violence and the number of casualties in these conflicts make the country syria become unstable and safe so that citizens syria opt out of the country and entry into the country of Turkey as refugees. In this respect, Turkey needs help from countries and international organizations in addressing this issue.This research theoretically has built with pluralism perspectives on International Relations and supported by the International Organization, and also the concept of human security. Formulation of all the arguments, facts and theoretical framework in this research was guided by qualitative descriptive explanation methods. Scope of this research is the Turkish efforts in tackling the refugees from Syria.This research also proves that Turkish efforts in tackling the problem of Syrian refugees in cooperation with countries and international organizations is good.Cooperation undertaken by Turkey such as by country, united nations and the European Union. Includes involvement of UNHCR, UNICEF, UNDP, IOM, WHO and WFP. With such cooperation makes Turkey helped in addressing this issues of Syrian refugees.Keywords: Cooperation, Syrian Refugees, Turkish efforts